1996
DOI: 10.1210/jcem.81.10.8855802
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic polypeptide administration improves abnormal glucose metabolism in patients with chronic pancreatitis.

Abstract: Chronic pancreatitis (CP) is associated with lowered plasma levels and a blunted nutrient-induced release of pancreatic polypeptide (PP). To investigate the possible role of PP on glucose metabolism, we studied male patients with documented CP (n = 5) and obesity-matched control subjects (NL) (n = 6). Hepatic glucose production (HGP) and overall glucose disposal rates were determined by [3-3H]glucose infusion during a hyperinsulinemic-euglycemic clamp during three separate admissions. Basal rates of HGP were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 3 publications
0
41
0
1
Order By: Relevance
“…When PP was infused along with insulin, suppression of hepatic glucose production significantly increased to about 65%. Using similar techniques to those employed in dogs, Brunicardi et al demonstrated similar findings in humans with chronic pancreatitis (18).…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…When PP was infused along with insulin, suppression of hepatic glucose production significantly increased to about 65%. Using similar techniques to those employed in dogs, Brunicardi et al demonstrated similar findings in humans with chronic pancreatitis (18).…”
Section: Discussionmentioning
confidence: 77%
“…Obese subjects with abnormal oral glucose tolerance demonstrated elevated basal levels of PP and an exaggerated increase in PP levels in response to glucose stimulation. Brunicardi and Sun indicated that PP might play an important role in the regulation of glucose metabolism by affecting the hepatic response to insulin (3,18). Sun et al examined pancreatogenic diabetes in a canine model of chronic pancreatitis (3).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, PP administration has been shown to improve glucose homeostasis and conservative surgical procedures that preserve the head of the pancreas appear to reduce the incidence of postoperative diabetes. 33 The release of incretin hormones may be disordered in DEP, leading to a suboptimal post-prandial insulin secretion. In normal physiology, fatty acids and other nutrients cause the release of glucagon-like peptide-1 (GLP-1) from intestinal L cells in the ileum and large intestine and glucose-dependent insulinotropic polypeptide from K cells of the small intestine.…”
Section: Diabetes Of the Exocrine Pancreasmentioning
confidence: 99%
“…This is caused by b-cell dysfunction following pancreatic inflammation or by absolute b-cell loss (5,6). In addition, pancreatic polypeptide upregulates insulin receptor expression in the liver, and its loss can lead to hepatic insulin resistance (7), an important physiological difference between diabetes of the exocrine pancreas and type 1 diabetes. Glucagon production from pancreatic a-cells is also diminished, which may explain the episodes of severe hypoglycemia that are reported in some patients (8,9).…”
mentioning
confidence: 99%